Increasing Uzbekistan’s export capacity through economic reforms - Sayfullaeva Nigora Fayzulla qizi (THE INNOVATION ECONOMY, 2026)
The article broadly describes the development of Uzbek exports, taking into account not only local reforms but also foreign experiences. The main emphasis is on studying the experiences of reputable foreign and local enter prises in Uzbekistan, conducting surveys among enterprises, identifying existing shortcomings and suggesting solu tions to them.